The ‘Hebridean Marsh-Orchid’: Nomenclatural and conceptual clarification of a biological enigma - Bateman, R. M.; Denholm, I. (Edinburgh Journal of Botany, 2010)
The ‘Hebridean Marsh-orchid’ is a controversial dactylorchid taxon currently regarded as endemic to the island of North Uist in the Scottish Hebrides. Re-evaluation of past taxonomic treatments reveals that none of its three names – Dactylorhiza majalis (Reichenbach f.) P. F. Hunt & Summerhayes subsp. scotica Nelson (1976, 1979), D. majalis subsp. occidentalis (Pugsley) Soó var. ebudensis Wiefelspütz (in Landwehr, 1977), and D. majalis subsp. occidentalis var. scotica (Nelson) R. M. Bateman & Denholm (1983) – has been validly published. We herein legitimize D. majalis subsp. occidentalis var. ebudensis Wiefelspütz ex R. M. Bateman & Denholm, presenting for the first time full details of its lectotype. However, we also note that this nomenclatural clarification has no relevance to determining the most appropriate rank for, and biological significance of, this taxon, which is one of many doubtfully distinct ‘critical’ taxa of dactylorchids that occur in western and northern regions of the British Isles. Taxonomic opinions expressed on these populations to date have been based on sparse, qualitative, and often contradictory data, and most lacked an explicit conceptual framework. We outline a more rigorous analytical protocol.